Iron Metabolism A Double-Edged Sword - Zakaria, Marwa; Hassan, Tamer (Biochemistry, 2022)
Iron is an essential element for numerous fundamental biologic processes. Iron-containing proteins are required for vital cellular and organismal functions including oxygen transport, mitochondrial respiration, intermediary and xenobiotic metabolism, nucleic acid replication and repair, host defense, and cell signaling. However, excess iron is toxic. This book provides a comprehensive overview of the essential role of iron in biology, the regulation of systemic and cellular iron homeostasis, and how imbalances in iron homeostasis contribute to disease.